Psychological features of women's codependency during the midlife crisis - A. Lymankina (Mukachevo State University, 2023)
The relevance of the research is conditioned upon the rapid spread of the problem of codependency, which has a destructive impact on the psychological state, and social and personal development of a person. The purpose of the research is to determine the psychological traits of codependent women in the period of midlife crisis. The research methodology is based on the methods of critical analysis, synthesis and generalisation of scientific and methodological literature. In the course of the study, the concept of codependence is defined, and the factors of its development are identified. It has been established that the main factor that becomes a prerequisite for the emergence of codependency is upbringing in a dysfunctional family. The psychological features of women's codependency and their manifestations are described. It has been established that codependent women are characterised by low self-esteem, a desire to control others, using psychological defence mechanisms, self-sacrifice, and caring for others, forgetting about their own needs and feelings. The author analyses the midlife crisis as a factor of personality transformation and a period with a high opportunity to free oneself from codependency. It is determined that during a midlife crisis, a person tries to reassess their life, achievements, and behavioural patterns. The author argues that the midlife crisis can have both destructive consequences, including the loss of the meaning of life, and constructive ones, which are manifested in the discovery of new meanings. The results of the scientific research are designed to generalise theoretical data on the problem of codependency and identify the psychological traits of codependent women. The theoretical significance of the research lies in the systematisation of scientific approaches to the study of codependent personality and the identification of psychological traits of codependent women in the period of midlife crisis.